Gene Expression in Oligodendroglial Tumors - Elisabeth J. Shaw; Brian Haylock; David Husband; Daniel du Plessis; D. Ross Sibson; Peter C. Warnke; Carol Walker (Analytical Cellular Pathology)
Background: Oligodendroglial tumors with 1p/19q loss are more likely to be chemosensitive and have longer survival than those with intact 1p/19q, but not all respond to chemotherapy, warranting investigation of the biological basis of chemosensitivity.